Additive Interactions Between School Bullying Victimization and Gender on Weapon Carrying Among U.S. High School Students: Youth Risk Behavior Survey 2009 to 2015. Issue 19 (October 2021) - Pontes, Nancy M. H.; Pontes, Manuel
The recent increase in the number of school shootings in the United States is a great concern. Consistent with General Strain Theory, previous research suggests that high school students who perpetrate gun violence have often experienced bullying victimization. This research investigated the interaction between gender and school bullying victimization on gun carrying, weapon carrying, and weapon carrying at school. Estimates of additive interaction were reported as recommended by the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines and compared with the estimates of multiplicative interaction. Data were used from a nationally representative survey of 61, 042 U.S. high school students. Secondary analysis of pooled cross-sectional data from the 2009, 2011, 2013, and 2015 Youth Risk Behavior Survey was done, using R to estimate interactive effects on an additive scale between male gender and school bullying victimization on weapon carrying. A significant association was found between school bullying victimization, and gun and weapon carrying. Estimates of additive interaction show that the relationship between school bullying victimization and gun or weapon carrying is significantly greater among males than females as predicted by General Strain Theory . School bullying victimization increases the rate of gun and weapon carrying among all students, and especially among male students. Most mass school shooters are male and most of them experience some form of bullying victimization. Consequently, bullying prevention is likely to be important in a national effort to reduce gun and weapon violence in U.S. schools. This research also illustrates why estimates of adjusted risk differences and additive interactions should be reported for interpersonal violence research.